"The 11 +" Warm-Up Program in Female Soccer Players and the Morpho-Physiological Changes Generated after its Implementation - Burboa, Jair; Valles, Camilo; Ormeño, Nelson; Barahona, Maximiliano; Zamorano, Alvaro; Hinzpeter, Jaime (International Physiology Journal, 2018)
Objective: Use "The 11 +" warm-up program in female players of the National Chilean Sub-17 Football team in order to analyze morpho – physiological variables. The implementation of this training program will generate morpho – physiological changes between players exposed. Federation International Football Association (FIFA) created a training program known as the "11+", designed to amend morpho-functional parameters such as lower extremity alignment, strength, intra, and inter muscular coordination and balance, among others. Subjects: Information indicates that injuries are a serious cause of concern for the soccer clubs and therefore, it is necessary to introduce the prevention programs. Methods: 20 female players of the National Chilean Sub-17 Soccer Team, from 14 to 17 years, who trained from March 2017 to January 2018. The “The 11+” warm-up program was considering an independent variable and thigh circumference, jumping ability, speed and balance are considered dependent variables. We use The STATA 11.1 SE (Statistics / Data Analysis) program for the statistical. Results: After implementing the “The 11+” program, significant changes (p < 0.05) were observed in the morphological variables of thigh circumference and functional speed. Concerning the functional variables of jump and balance, favorable but not statistically significant. Conclusions: Application of the "The 11 +" warm-up program for 3 months in addition to proper training, generated morpho – physiological changes associated with an increase in thigh circumference and an improvement in speed. The practical utility is to improve morpho-physiological characteristics of players in a competitive area and thereby to improve the utility of athletic performance indirectly.
Keywords: Warm up program; Morpho-physiological changes; Injuries.